SISTEM PENUNJANG KEPUTUSAN PEMILIHAN PROYEKTOR MENGGUNAKAN METODE WASPAS DENGAN PENDEKATAN SKALA BOBOT DAN KRITERIA - Andi Atmaja Kusuma Wijaya; Agus Sidiq Purnomo (LPPM Unbaja, 2025)
Choosing a projector is a challenge because of the many specifications and features it has. Various factors such as resolution, brightness level, contrast ratio and price must be considered so that decisions are made according to what is needed. Errors in projector selection can increase operational costs and effectiveness of use. To overcome this problem, a decision support system was developed using the WASPAS method to assist in the selection process which provides accurate results and considers the weight of relevant criteria. WASPAS provides flexibility in assessing alternatives based on several given aspectsThis research is designed to assist in projector selection based on several criteria. The criteria data will be processed using the WASPAS method to provide alternative rankings that suit user needs. This system provides the best alternative with high accuracy and can make decision making easier and minimize the risk of errors.With this method, it is hoped that the projector selection process will be faster and more efficient. Apart from that, this system can provide practical benefits in increasing budget effectiveness and improving the performance of the devices used.